FIGURE 16 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 16. (A–G) Cretaxinus hurumi gen. et sp. nov. (A) Lateral view of left valve of articulated internal mould, showing a distinct, triangular shape. (B–C) Anterior views showing shape and size of lunule and anterior pedal retractor scar. (D) Dorsal view showing shape of the posterodorsal margin. (E–F) Cardinal and posterodorsal portion of left valve internal mould shell showing posterior adductor muscle scar with distinct notch on anteroventral margin and posterior pedal retractor scar. (G) Silicone rubber cast of (E–F) showing small and elongated groove, possibly ligament groove. (H–P) Pseudotrapezium aff. groenlandicum (Spath, 1936). (H) Lateral view of the shell showing the outline and carina. (I–J) Anterior and posterior views of articulated specimen with most of the shell preserved. (K) Dorsal view showing flattened posterior area, two carinae and very thin shell. (L–M) Anterior view of articulated specimen with some preserved shell, showing deep and small lunule and rounded anterior adductor muscle scar. (N–O) Oblique posterior view showing weak pallial line and weakly impressed posterior adductor muscle scar. (P) Right valve dentition and large hinge plate. (A–D) PMO 217.540, (E–G) PMO 217.175, (H–K) PMO 226.632, (L–M) PMO 226.633, (N–O) PMO 226.635, (P) JUE no. 15926. Scale bars 10 mm (A–G), 5 mm (H–P). : Published as part of Hryniewicz, Krzysztof, Little, Crispin T.S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on page 41, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112